(untitled) (International Association of Biologicals and Computational Digest, 2022)
Hydrogen peroxide (H2O2) plays an important role in fruit growth and its preservation. But too much hydrogen peroxide (H2O2) can be harmful to fruit cells. According to previous studies, the fruits contain an enzyme called catalase which converts the extra H2O2 into water and oxygen (O2). Therefore, an experiment conducted to find the presence or absence of catalase enzyme in various fruits as well as the activity of catalase was compared among the different fruits; including Apple, banana, pineapple, strawberry, watermelon, dragon fruit, kiwi and papaya. When an additional hydrogen peroxide (H2O2) (6% concentration) was added to the test tube containing the fruit sample, O2 bubbles were found in the test tube, which showed that the catalase enzyme in the fruit pieces decomposed the excess hydrogen peroxide (H2O2) in the test tube, resulting in the release of water (H2O) and oxygen (O2). The According to the present study, the highest amount of catalase enzyme was found in a banana while the lowest was found in watermelon.